Abnormal p38α mitogen-activated protein kinase signaling in dilated cardiomyopathy caused by lamin A/C gene mutation - MUCHIR, Antoine; WEI WU; CHOI, Jason C; IWATA, Shinichi; MORROW, John; HOMMA, Shunichi; WORMAN, Howard J (Human molecular genetics, 2012)
We previously interrogated the transcriptome in heart tissue from Lmna(H222P/H222P) mice, a mouse model of cardiomyopathy caused by lamin A/C gene (LMNA) mutation, and found that the extracellular signal-regulated kinase 1/2 and Jun N-terminal kinase branches of the mitogen-activated protein (MAP) kinase signaling pathway were abnormally hyperactivated prior to the onset of significant cardiac impairment. We have now used an alternative gene expression analysis tool to reanalyze this transcriptome and identify hyperactivation of a third branch of the MAP kinase cascade, p38α signaling. Biochemical analysis of hearts from Lmna(H222P/H222P) mice showed enhanced p38α activation prior to and after the onset of heart disease as well as in hearts from human subjects with cardiomyopathy caused by LMNA mutations. Treatment of Lmna(H222P/H222P) mice with the p38α inhibitor ARRY-371797 prevented left ventricular dilatation and deterioration of fractional shortening compared with placebo-treated mice but did not block the expression of collagen genes involved in cardiac fibrosis. These results demonstrate that three different branches of the MAP kinase signaling pathway with overlapping consequences are involved in the pathogenesis of cardiomyopathy caused by LMNA mutations. They further suggest that pharmacological inhibition of p38α may be useful in the treatment of this disease.